A imagem cinematográfica como objeto colecionável: o colecionador na era digital. - Soraia Nunes Nogueira (2004)
The Project of Master's degree in Visual Arts has as intention to accomplish a study regarding what makes the film to have and to be something collectible. Starting from the study of who is the collector we deepened the analysis for the movies collectors, approaching his/her importance in the preservation of the movies, their relationships with the cinematheques and studios and their characteristics for the process of to collect and to classify their objects. We tried to describe the formation of the film industry in Hollywood and their great studios, that created a characteristic language to urge the desire to collect their images. And, among of this process, we detailed several characteristics of the products, attractive for the collectors. We approached the horror focusing the classic monsters of the Universal as base for one of the goods that more generated collectors, beside the one of science fiction. And, as practical result, we created, starting from the independent production The chaos trilogy, products of collectors' interest, given the public's answer observed during the long production of the animation.